Assessment Of Some Heavy Metals in Some Plastic Toys Collected from Zawia City Markets - Samir A. Karshman; Mabrouka M. Hamzah; Najah Y.Baroud; Rania A. Alrwesse; Abtisam S. Aljarmi (African Journal of Advanced Pure and Applied Sciences, 2025)
By fostering imagination, creativity, and the development of a variety of skills, toys are essential to a child's growth. Nevertheless, the presence of dangerous heavy metals like lead (Pb) and copper (Cu) in toy materials, especially plastic toys, can present serious health risks. This study sought to determine the concentrations of heavy metals (Cu, Pb, Cd) in plastic toys gathered from different Libyan markets in the city of Zawia. Ten distinct toy categories including jewelry, building blocks, balls, and animals were sampled. The concentrations of lead and copper in the samples were determined using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES). According to the findings, the concentrations of lead varied from 0.37 mg/kg to 10.4 mg/kg, with an average of 2.14 mg/kg, and for copper varied from 0.56 mg/kg to 15.4 mg/kg, with an average of 4.613 mg/kg. The highest concentrations of lead and copper were found in colorful toys, even though the lead levels in all toy samples were below the 90 mg/kg maximum allowable limit. Due to their hand-to-mouth behavior and the metals' bioaccumulation, the study also emphasized the possible health risks of heavy metal exposure, particularly for younger children. It is advised that regulations be put in place to keep an eye on and manage the levels of heavy metal contamination in toys for kids. The results of this study help to increase public awareness about toy safety.